St. Kitts and Nevis : 2016 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights that economy of St. Kitts and Nevis continued its strong growth at about 5 percent, recording the strongest growth in the region during 2013-15. Strong growth has been underpinned by construction and tourism sector activity and their favorable spillovers on the rest of the economy, supported by surging inflows from its Citizenship-by-Investment (CBI) program. Large CBI inflows continued in 2015, albeit at a slower pace. The medium-term outlook is positive, but remains dependent on developments in CBI inflows. Growth is expected to moderate to 3.5 percent in 2016 and 3 percent, on average, over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet